Retrospective analysis of pediatric sepsis and the burden of antimicrobial resistance in Duhok, Kurdistan Region of Iraq - Ibrahim, Delveen R.; Saadi, Abdulrhaman T.; Yahya, Nizar B.; Ibrahim, Marwa S.; Saeed, Ali Y.; Abdulaziz, Sawsan S.; Hasqyal, Revan Y.; Alarsalani, Berivan K.; Ibrahim, Khalid S. (Frontiers in Pharmacology, 2024)
Sepsis is a life-threating complication among pediatric patients. This study aims primarily to investigate sepsis causative bacteria, their antimicrobial resistance profile, and to check the change of antimicrobial resistance trend for some selected bacteria.In addition, to evaluate the incidence of sepsis and related mortality rate. Besides, to evaluate the effectiveness and outcome of the treatment regimes in sepsis pediatric patients. A retrospective analysis was conducted on a four-year data (2018)(2019)(2020)(2021) collected from three Intensive Care Units of Hevi Pediatric Teaching Hospital. Sepsis screening involved clinical detection and confirmed by blood culture. A total of 520 out of 1098 (47.35%) blood samples showed positive microbial growth. Sepsis rate's reduction noticed during COVID-19 pandemic period. Coagulase-Negative Staphylococci (CoNS) and Klebsiella pneumonia were the most common isolated bacteria. A notable variation of antimicrobial resistance trend observed among sepsis causing bacteria. Obviously, the sepsis empirical treatment recommended by WHO was ineffective, as certain bacteria exhibited 100% resistance to every antibiotic tested. The mortality rate significantly increased from 1.3% in 2018 to 16.5% in 2021.The antimicrobial resistance profile for sepsis causing bacteria sending an alarm for expecting the worst. Thus, to avoid treatment failure, it is essential to monitor antimicrobial resistance in pediatric patient.